Spatial Distribution Analysis of Geotechnical Properties (Elastic Modulus, Cohesion, and Internal Friction Angle) in Soil Layers of Bengkulu City - Hanipa, Rerisa Al; Kamal, Thomas Mustafa; Fikri, Muhammad Haikal; Mase, Lindung Zalbuin; Misliniyati, Rena; Supriani, Fepy; Refrizon, Refrizon (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
This study investigates the spatial distribution of key geotechnical parameters—namely modulus of elasticity, cohesion, and internal friction angle—in the dominant soil types of Bengkulu City, Indonesia. Given the region’s complex geological structure and vulnerability to seismic activity, accurate assessment of soil characteristics is essential to support infrastructure development and mitigate geotechnical risks. Bengkulu lies between two active tectonic faults, making soil behavior analysis a crucial component of earthquake-resistant design. A total of 215 geotechnical data points were compiled from previous field investigations, covering a wide range of lithologies, including sandy soils, clay deposits, and various rock layers. The geotechnical parameters were spatially interpolated using the Inverse Distance Weighting (IDW) method to generate distribution maps that visualize the variation across different soil layers. This method was selected for its simplicity, effectiveness, and ability to provide weighted estimates based on spatial proximity. The analysis reveals that soils in the southern coastal region generally exhibit lower values of modulus of elasticity and cohesion, indicating a higher potential for deformation and shear failure. In contrast, central and northern areas tend to show higher geotechnical strength parameters, suggesting relatively stable ground conditions. The internal friction angle also increases with depth and material density, with hard rock zones showing the highest values. These findings contribute to the understanding of soil behavior in Bengkulu City and offer valuable insights for geotechnical engineers, urban planners, and disaster mitigation authorities. The spatial analysis of soil strength parameters provides a foundation for more resilient infrastructure planning and can be used as a reference for similar studies in other high-risk seismic regions.